PENYULUHAN PENANGANAN LIMBAH HASIL PEMBUATAN KAIN TENUN TRADISIONAL DI KELURAHAN 10 ULU KERTAPATI PALEMBANG - Selastia Yuliati; Andanti Pratiwi; Anisa Nabillah; Anisah Luthfiyah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
South Sumatra songket woven fabric is made through a dyeing process using a lot of dyes including Reacsol Yellow P-G or Rhodamin B which uses a lot of phenol and organic compounds. These dyes when disposed of directly will cause pollution. The purpose of this activity is to provide counseling on how to handle the waste from the weaving industry. The method applied in this activity is conducting surveys, making waste treatment tanks, and followed by questions and answers and counseling at partner locations. The results of this activity obtained one unit of a waste treatment tub equipped with advanced purification equipment, it is hoped that with this tool the level of pollution caused by the disposal of waste from the weaving industry in the form of dyes in South Sumatra can be reduced.